PENGEMBANGAN MODUL PEMBELAJARAN FISIKA BERBASIS LEARNING CYCLE 5E POKOK BAHASAN GETARAN HARMONIS UNTUK SISWA SMA - Rafidatul Anisa; Rayendra Wahyu Bachtiar; Bambang Supriadi (JURNAL PEMBELAJARAN FISIKA, 2018)
Abstract The use of modules and organizing a good material helped students tounderstand the material and students were able to achieve the results of the study.Integrated learning cycle 5E model into a module was one of the constructivistapproach that prioritizes the student as the center of the learning activities. Thisresearch resulted in a product module of learning physics-based 5E learning cycle inharmonious vibration subject for high school students. This research used 4-D designmodel of development. The results of the validation 3.98 and included in criteria quitevalid. The precentage of the effectiveness this module was 62.96% and included incriteria of effective. The practicality of the module retrieved the percentage of 85.2%,so it concluded that the use of the learning modules developed a very positive responsefrom students.Keyword: module based learning cycle 5E, validation, effetiveness, practicallity